Guerras de memoria en Francia y su uso político por Nicolas Sarkozy - Garcés González, Jorge (Historiografías, 2019)
In this study, we examine the way through which France is facing some traumatic pasts during the presidential term of Nicolas Sarkozy (2007-2012), and particularly the historiographical debates, public controversies and social demands which memory wars conceal on two this topics: the appropriation of the memory of the young communist Guy Môquet, assassinated by the Nazis during the Second World War, and his electoral instrumentalization of the Algerian war. The Fifth Republic has developed an institutional policy based upon the promulgation of a series of memory laws which led to numerous reservations within the academic community. This process, and above all the political use of history carried out by Sarkozy, forms the central core in this work, tributary of methods of the so-called history of the present.